Internet Of Things-Based Orchid Plant Watering Tool - Irwan Solikudin; Syamsudduha Syahrorini (Procedia of Engineering and Life Science, 2021)
The orchid flower is an ornamental plant that has a lot of interest. For orchid cultivation, there are many things that need to be monitored, including the watering process. Referring to this, an Internet of Things (IoT) -based orchid watering device was made which uses Arduino as a microcontroller, the yl-69 sensor as a soil moisture reader, the DHT11 sensor as a temperature reader, the float swith sensor as an automatic reservoir and an omron timer as a timer for administration. vitamin. All data read by the sensor is sent to the Thingspeak webserver and forwarded to the MIT App Invertor application installed on the smartphone. This tool is made to make it easier for a cultivator to monitor watering plants remotely via an application on a smartphone. After taking data for about two weeks, the sensor readings were obtained, including the yl-69 sensor in wet conditions which has a standard deviation of 0.89 and dry conditions 1.18, the DHT11 sensor has a standard deviation of 0.4 for temperature. For the development of orchid plants, it shows quite good results, it is shown from the stems and leaves of the plants that begin to elongate and grow thick.